Metaphorical Analysis of Software Clone Detection Techniques based on Dimensions and Metrics - Bharti, Sarveshwar; Singh, Hardeep (International Journal of Computer Sciences and Engineering, 2018)
In spite of having limited benefits, software clones mostly have negative impact on software quality, more specifically on software maintenance and thus diminishing software quality and raising the maintenance cost. Not all the clones are possible to remove, but, if possible clones need to be removed from the software system. To remove clones, we need to first detect this duplication in the code base. Literature lists various clone detection techniques that are used to detect duplication in software system. To have a better clone detection technique in future or to select from the available clone detection technique, these available techniques found in literature need to be analyzed. This paper attempts to comparatively analyze the clone detection techniques available in literature and thus will present a future scope as well as the recourse based on the analysis for selection of any particular technique.